Synthesis, Characterization, Liquid Crystalline and Antibacterial Properties of Pyrimidine Derivatives - Tasya Ezzati, Binti Busrah @ Affendi (unimas, 2017)
Pyrimidine and its derivatives are commonly synthesized due to their reactive and rigid which employ in many applications such as liquid crystal and biological properties. A series of pyrimidine derivatives bearing alkyl chain (50a-c, 53a-c) and halogen 56a-f substituents has been successfully synthesized via nucleophilic reaction with 17-78% yield. The alkylated (49a-c, 52a-c) and halogenated (55a-f) chalcone were earlier prepared via Claisen Schmidt condensation prior to the synthesis of pyrimidine. The successfully synthesized pyrimidine derivatives were illustrated in the FTIR and 13C NMR spectra whereby the presence of absorptions and resonances attributed to C=S and C-N group while 1H NMR showed resonances of singlet for N-H group. The DSC thermogram showed thermotropic liquid crystal properties of pyrimidine 53a-b gave direct transition from Cr-I phase while 53c exhibited Cr-Cr and Cr-I transition. Antibacterial studies against bacteria Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus) of pyrimidine derivatives bearing alkyl group (53a-c) however not exhibit antibacterial activities towards both bacteria.